2023
DOI: 10.1108/dlp-04-2023-0032
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the use of mobile technologies for learning: an empirical study of library and information science (LIS) students

Abstract: Purpose The use of mobile technologies and learning devices has been increasing in every field of life, and library and information sciences are no exception. This study aims to explore the perceptions of library and information science (LIS) students regarding mobile learning (m-learning) along with their primary purposes, social media applications, advantages, disadvantages, barriers, impact and overall satisfaction with using these devices. Design/methodology/approach A survey method was used, and data wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 28 publications
0
0
0
Order By: Relevance
“…In their study, Ashiq et al (2023) concluded that traditional learning often poses challenges for students in accessing books and learning resources due to the limitations of physical libraries and textbooks. In contrast, mobile-based learning offers convenient access to a wide range of learning resources via apps and the Internet, allowing students to download e-books, learning materials, and videos online [33]. Mobile-based learning has become a solution to the limitations of traditional educational methods.…”
Section: Introductionmentioning
confidence: 99%
“…In their study, Ashiq et al (2023) concluded that traditional learning often poses challenges for students in accessing books and learning resources due to the limitations of physical libraries and textbooks. In contrast, mobile-based learning offers convenient access to a wide range of learning resources via apps and the Internet, allowing students to download e-books, learning materials, and videos online [33]. Mobile-based learning has become a solution to the limitations of traditional educational methods.…”
Section: Introductionmentioning
confidence: 99%